George Lippard's 'Theatre of Hell': Apocalyptic Melodrama and Working-Class Spectatorship in the Quaker City - D'Alessandro, Michael (J19, 2017)
In a January, 1842, article for Philadelphia's Democratic paper The Spirit of the Times, the author George Lippard depicts a visit from a "bona fide spirit, with a tail and two horns." The devilish creature bestows upon Lippard's city-reporter alter ego, "Flib," a magical ring that "renders the wearer invisible" and allows him to observe silently the secret exchanges and exploitations of antebellum Philadelphia. Previous Lippard scholars have acknowledged a link between the author's work and theater, particularly the period's dominant theatrical genre of melodrama. Here, D'Alessandro argues that via central set-pieces throughout Quaker City, Lippard attempts to invoke working-class spectatorial experiences and hence to unite a community of diverse workers within a failing Philadelphia social order.